Answer:
n = -6
Step-by-step explanation:
-3n + 9 = 27 (Given)
-3n + 9 - 9 = 27 - 9 (Subtraction Property of Equality)
-3n = 18 (Simplify)
(Division Property of Equality)
n = -6 (Simplify)
Answer:
100ft
Step-by-step explanation:
H over S
H over 125 then 4 over 5
cross Multiply would give you
5H = 500
500 ÷ 5 is 100
Answer:
x = 3
Step-by-step explanation:
Given the 2 equations
x + y = 3 → (1)
2x - y = 6 → (2)
Adding the 2 equations term by term eliminates the y- term, that is
3x = 9 ( divide both sides by 3 )
x = 3
Ok, so the function form is y = a * bx.
Substitute in the values:
750 = a * b5
and
48 = a * b2
Then divide the two equations:
750/ 48 = (a * b5) / (a * b2)
So:
15.625 = b3
Take the cube root of both sides:
2.5 = b
Now, substitue b into one of the equations (the one with 48 has smaller numbers and is easier to work with.)
48 = a * 2.52
Simplify.
48 = a * 6.25
Divide both sides by 6.25
7.68 = a
Now substitute in a and b to write the exponential function:
y = 7.68 * 2.5x